2013
DOI: 10.1093/nar/gkt957
|View full text |Cite|
|
Sign up to set email alerts
|

Detection of G-quadruplex DNA in mammalian cells

Abstract: It has been proposed that guanine-rich DNA forms four-stranded structures in vivo called G-quadruplexes or G4 DNA. G4 DNA has been implicated in several biological processes, but tools to study G4 DNA structures in cells are limited. Here we report the development of novel murine monoclonal antibodies specific for different G4 DNA structures. We show that one of these antibodies designated 1H6 exhibits strong nuclear staining in most human and murine cells. Staining intensity increased on treatment of cells wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
338
2
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(357 citation statements)
references
References 60 publications
13
338
2
4
Order By: Relevance
“…Binding of 1H6 antibodies to G-rich oligonucleotides [(TTAGGG) 4 ] was also observed. Marginal binding to the singlestranded DNA (ssDNA) was recorded, as previously reported (41,42). These results confirm that under our conditions, both the telomeric and myc oligonucleotides fold into G-quadruplexes.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Binding of 1H6 antibodies to G-rich oligonucleotides [(TTAGGG) 4 ] was also observed. Marginal binding to the singlestranded DNA (ssDNA) was recorded, as previously reported (41,42). These results confirm that under our conditions, both the telomeric and myc oligonucleotides fold into G-quadruplexes.…”
Section: Resultssupporting
confidence: 91%
“…The ELISA was performed with the BG4 or 1H6 antibodies that bind specifically to the G-quadruplex structures (41,42). Biotinylated oligonucleotides of the Myc promoter (5=-Biosg/ACTACT ACTGGGGAGGGTGGGGAGGGTGGGGAAGG-3=) and telomeric repeats (5=-Biosg/ACTACTACTGGTTAGGGT TAGGGTTAGGGTTAGGGTTAG-3=), which fold in G-quadruplex, and ssDNA (5=-Biosg/ACTACTACTGGCAT AGTGCGTGGGCG-3=), which supports formation of G-quadruplexes, were purchased from IDT (Coralville, Iowa, USA).…”
Section: Methodsmentioning
confidence: 99%
“…To date, the strongest arguments have been provided by quadruplex-specific antibodies, 7-9 including BG4 8 and 1H6. 9 However, an important limitation of immunodetection is its restriction to fixed and permeabilized cells (to allow entry of cell-impermeable antibodies), therefore limiting the detection of quadruplexes to cells whose morphological integrity is impaired. Rodriguez et al reported on an elegant way to tackle this issue, performing cell-based chemical labeling of a quadruplex ligand (PDS-α) bound to its genomic targets prior to cell fixing, thus enabling the identification of quadruplexes in functioning cells.…”
Section: Introductionmentioning
confidence: 99%
“…G4 structures are known to be stabilized by large monovalent cations, preferably potassium 3 . G4-DNA structures were recently detected in cells 4,5 . Computational analysis showed that G4-DNA sequences are predominantly located within telomeric regions and promoter regions (within 1kb upstream of the transcription start site, TSS) 6,7 , indicating strongly that G4 structures have roles in the regulation of gene expression.…”
mentioning
confidence: 99%